2010
DOI: 10.2737/rmrs-gtr-251
|View full text |Cite
|
Sign up to set email alerts
|

Risk of impaired condition of watersheds containing National Forest lands

Abstract: T h o ma s C. B r o wn a n d P a me l a F r o e mk e You may order additional copies of this publication by sending your mailing information in label form through one of the following media. Please specify the publication title and series number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The refined measures allow a more-precise assessment of risk but require much additional data processing (e.g., to delineate riparian areas). The use of more-refined measures is not uncotnmon (Wang et al 2008, Brown andFroemke 2010). However, Falcone and colleagues (2010) recently used independent measures of watershed degradation to assess the utility of different sets of Stressors and found that the refined measures do not tend to contribute much to an overall assessment of risk, in part because of the high correlations between the coarse and the corresponding refined measures.…”
Section: Stressorsmentioning
confidence: 94%
“…The refined measures allow a more-precise assessment of risk but require much additional data processing (e.g., to delineate riparian areas). The use of more-refined measures is not uncotnmon (Wang et al 2008, Brown andFroemke 2010). However, Falcone and colleagues (2010) recently used independent measures of watershed degradation to assess the utility of different sets of Stressors and found that the refined measures do not tend to contribute much to an overall assessment of risk, in part because of the high correlations between the coarse and the corresponding refined measures.…”
Section: Stressorsmentioning
confidence: 94%
“…Land uses in Great Plains watersheds include livestock grazing, row-crop agriculture, planted pasture, urban areas, roads, dams and reservoir development, and energy development (Brown and Froemke 2010;Reeves and Mitchell 2012;Smith et al 2014). The proportion of rangeland permanently converted to other uses varies from 8 percent in Wyoming to 56 percent in Nebraska; at the county level, loss of rangeland varies from 0 to 100 percent (see figure 11 in Reeves and Mitchell 2012).…”
Section: Current Status and Human Influences_________________________mentioning
confidence: 99%
“…Almost all of the Shoshone watersheds are currently classified as in good to excellent condition (Brown and Froemke 2010; USDA Forest Service 2011a). Those watersheds in • Precipitation and snowpack decline…”
Section: Current Conditionsmentioning
confidence: 99%
“…Problems with sediments, nutrients, and toxins have been ranked very low for Shoshone watersheds (Brown and Froemke 2010). Water quality in a few watersheds is of concern due to mining activity and these watersheds are targeted for mitigation through watershed improvement plans (USDA Forest Service 2011a).…”
Section: Current Conditionsmentioning
confidence: 99%